Analisis Pengaruh Soundscape terhadap Kenyamanan Pengunjung di Taman Kota Sewaka Dharma, Denpasar, Bali - Sriwidari, Ida Ayu; Semarajaya, Cokorda Gede Alit; Sukewijaya, I Made (Jurnal Arsitektur Lansekap; Vol.9, No.2, Oktober 2023, 2023)
Analysis of the Effect of Soundscape on Visitor’s Comfort in Sewaka Dharma City Park, Denpasar, Bali . Sound is non-physical element that get less attention in creating sense of place. Very difficult to find good soundscape quality in urban landscape because of the negative impacts of noise. The existence of Sewaka Dharma City Park as public green open space should be a solution of these problems. This study aims to identify sound, analyze effect of soundscape on visitor’s comfort, and provide recommendation to improve the soundscape quality. The study method used is survey, with data collection technics used were observation, questionnaires, and literature study. The data analyzed by quantitative and descriptive analysis. Soundscape of this city park created by combination of natural sounds, human sounds, sounds and society, mechanical sound, and sound as indicator. The most dominant sound heard is the sound of vehicles. Measurement of SPL (Sound Preassure Level) reached 67.5 dB and it exceed the regulation for green open space. Sound assessment indicated natural sounds and sounds from worship place were considered as quite comfortable. Most of human sound and society are considered as not disturbing. Sounds that quite disturbing are people screaming, vehicles and horns. Noise control recommended in zone I and J, because it result the highest SPL and considered disturbing visitor’s activities, by adding barriers and filters with plants, pavement and water.